Secure sparse network coding for reliable routing in large scale DTMN - Chanyour, Tarik; Saadane, Rachid; Belkasmi, Mostafa (2015 Third International Workshop on RFID And Adaptive Wireless Sensor Networks (RAWSN), 2015)
Security issue occupies an important part in all communication system and especially for new generation networks. Among these networks, we find Delay Tolerant Mobile Networks (DTMNs) which are a class of useful but challenging networks. Combining Network Coding (NC) and clustering for routing in such networks gives more efficiency and copes with routing reliability problem among large scale networks. Our work's concern is to build a secure network coding scheme in the presence of eavesdroppers in large-scale DTMNs. Therefore, we used a cluster based routing protocol dedicated to DTMN specificities. In addition, we used Sparse Random Linear Network Coding (SRLNC) to feat low computational capabilities requirement in such networks. Furthermore, we addressed the packets retransmission decision problem for SRLNC with a fair trade-off throughput/overhead. The results are very encouraging and the proposed routing scheme has the advantage to be reliable as well as secure for large scale DTMN.